Surgery and emergency gastrointestinal endoscopy during the Covid-19 pandemic (2020)
Urgent gastrointestinal endoscopy (UGE) is a worldwide extended medical procedure, being the most frequent the upper and lower gastrointestinal bleeding and impaction of a foreign body the most common emergencies that require this technique1,2 . The activity in endoscopy units has been deeply affected by Covid-19 pandemic. In order to decrease the risk of infection, elective endoscopy has been stopped since “State of Alarm” was declared. However this restriction does not apply to UGE.